HOUSEHOLD FOOD SECURITY DURING THE COVID-19 PANDEMIC AS A RISK FACTOR FOR TODDLER STUNTING IN MAJENE - Dr. RAHMANIAH; Dr. MASNIATI; Dr. FAUZIAH; Dr. IKA PUTRI RAMADHANI (International Journal of Multidisciplinary Research and Studies, 2022)
Background: Stunting is a condition of failing to grow a toddler as an accumulation of chronic nutritional problems. Toddlers are categorized as stunting if the z-score is in the range of -3 to <-2SD based on the Height By Age index. Stunting children are more susceptible to disease and contribute to a child's below-average level of intelligence. The long-term effects of stunting can stunt economic growth as well as increase a nation's poverty. Objectives : To analyze household food security during the covid-19 pandemic with stunting events in toddlers aged 6-23 months in Pangali-Ali Village, Majene, West Sulawesi. Methods : This study is an observational study with a case-control study design. The population is all toddlers aged 6-23 months in Pangali-Ali Village of Majene Regency. The way of sampling is to use total sampling, so that the number of samples is equal to the population of 76 toddlers. The data was analyzed using SPSS with a chi square test. Results : Bi-variant analysis showed that household food security during the covid-19 pandemic had a significant association with stunting toddlers (p<0.05) and also obtained an odds ratio (OR) of 4.42. Toddlers who come from food-insecure households have a risk of stunting 4.42 times higher compared to toddlers who are in flood-resistant households. Conclusions: Household food security during the Covid-19 pandemic is a risk factor for stunting in toddlers in Majene in 2021. Children who are in food-insecure households are at risk of stunting at 4.42 times higher than children in flood-resistant households.